Fabrication and hemocompatibility assessment of novel polyurethane-based bio-nanofibrous dressing loaded with honey and Carica papaya extract for the management of burn injuries - Balaji A (Dove Medical Press, 2016)
Arunpandian Balaji,1 Saravana Kumar Jaganathan,2–4 Ahmad Fauzi Ismail,5 Rathanasamy Rajasekar6 1Faculty of Biosciences and Medical Engineering, Universiti Teknologi Malaysia, Johor Bahru, Malaysia; 2Department for Management of Science and Technology Development, Ton Duc Thang University, Ho Chi Minh City, Vietnam; 3Faculty of Applied Sciences, Ton Duc Thang University, Ho Chi Minh City, Vietnam; 4IJNUTM Cardiovascular Engineering Centre, Department of Clinical Sciences, Faculty of Biosciences and Medical Engineering, Universiti Teknologi Malaysia, Johor Bahru, Malaysia; 5Advanced Membrane Technology Research Center, Universiti Teknologi Malaysia, Johor Bahru, Malaysia; 6Department of Mechanical Engineering, School of Building and Mechanical Sciences, Kongu Engineering College, Tamil Nadu, India Abstract: Management of burn injury is an onerous clinical task since it requires continuous monitoring and extensive usage of specialized facilities. Despite rapid improvizations and investments in burn management, >30% of victims hospitalized each year face severe morbidity and mortality. Excessive loss of body fluids, accumulation of exudate, and the development of septic shock are reported to be the main reasons for morbidity in burn victims. To assist burn wound management, a novel polyurethane (PU)-based bio-nanofibrous dressing loaded with honey (HN) and Carica papaya (PA) fruit extract was fabricated using a one-step electrospinning technique. The developed dressing material had a mean fiber diameter of 190±19.93 nm with pore sizes of 4–50 µm to support effective infiltration of nutrients and gas exchange. The successful blending of HN- and PA-based active biomolecules in PU was inferred through changes in surface chemistry. The blend subsequently increased the wettability (14%) and surface energy (24%) of the novel dressing. Ultimately, the presence of hydrophilic biomolecules and high porosity enhanced the water absorption ability of the PU-HN-PA nanofiber samples to 761.67% from 285.13% in PU. Furthermore, the ability of the bio-nanofibrous dressing to support specific protein adsorption (45%), delay thrombus formation, and reduce hemolysis demonstrated its nontoxic and compatible nature with the host tissues. In summary, the excellent physicochemical and hemocompatible properties of the developed PU-HN-PA dressing exhibit its potential in reducing the clinical complications associated with the treatment of burn injuries. Keywords: electrospinning, porous morphology, surface energy, protein adsorption